Genetic structure of Trichinella britovi populations in wildlife of north and northeast Iran - Faramarz Koohsar; Saied Reza Naddaf; Hamed Mirjalali; Mehdi Mohebali; Mohammad Bagher Rockni; Ahmad Mahmoudi; Gholamreza Mowlavi (International Journal for Parasitology: Parasites and Wildlife)
Trichinella britovi is a parasite prevalent in the temperate regions of the vast Palearctic realm, including Iran. In this study, we investigated Trichinella infection in road-killed animals and carcasses in northern and northeastern Iran by artificial digestion. We assessed species identification and intraspecific genetic diversity using the markers 5S ribosomal DNA intergenic spacer (5S rDNA), internal transcribed spacer I (ITS1), and cytochrome c oxidase subunit I (COXI). Of the 80 encountered carcasses, 10 had Trichinella infection, including seven golden jackals, one wolf, one wild cat, and one wild boar. BLAST analysis exhibited the highest similarities with T. britovi sequences in the GenBank database, at 99.79%, 99.84%, and 100% for COXI, 5S rDNA, and ITS1, respectively. All 5S rDNA sequences were identical, while analysis using DnaSP software identified eight haplotypes in the ITS1 region and six haplotypes in the COXI sequences. The phylogenetic analysis based on the COXI marker clustered all T. britovi sequences, including those from Iran, into a distinct clade. Furthermore, this marker revealed shallow branching, dividing T. britovi sequences into two subclades. The first subclade, the “European” group, consisted exclusively of haplotypes from Poland. In contrast, the second subclade, “Euro-Asiatic,” included haplotypes of Asian and European origins. The Euro-Asiatic and European populations exhibited a 0.52% genetic distance while showing 0.59% and 0.15% intrapopulation divergence, respectively. Further studies involving specimens from other regions of Iran, particularly the southeast adjoining the Oriental zoogeographical zone, could provide additional insights into the molecular identity and population structures of T. britovi and potentially other species in Iran.